(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The interaction of platinum, rhodium and iridium tin-chloride complexes with N-(5-mercapto-1,3,4-thiadiazol-2-yl)-N’-propylurea groups covalently fixed on the silica gel surface has been researched. It is shown, that using of the tin-chloride complexes results in increasing of the platinum metals’ sorption degree and the sorbent’s sorption capacity and decreasing of the time of sorption equilibrium establishment.